The Prop1-like homeobox gene unc-42 specifies the identity of synaptically connected neurons - Emily G Berghoff; Lori Glenwinkel; Abhishek Bhattacharya; HaoSheng Sun; Erdem Varol; Nicki Mohammadi; Amelia Antone; Yi Feng; Ken Nguyen; Steven J Cook; Jordan F Wood; Neda Masoudi; et al. (eLife, 2021)
Many neuronal identity regulators are expressed in distinct populations of cells in the nervous system, but their function is often analyzed only in specific isolated cellular contexts, thereby potentially leaving overarching themes in gene function undiscovered. We show here that the Caenorhabditis elegans Prop1-like homeobox gene unc-42 is expressed in 15 distinct sensory, inter- and motor neuron classes throughout the entire C. elegans nervous system. Strikingly, all 15 neuron classes expressing unc-42 are synaptically interconnected, prompting us to investigate whether unc-42 controls the functional properties of this circuit and perhaps also the assembly of these neurons into functional circuitry. We found that unc-42 defines the routes of communication between these interconnected neurons by controlling the expression of neurotransmitter pathway genes, neurotransmitter receptors, neuropeptides, and neuropeptide receptors. Anatomical analysis of unc-42 mutant animals reveals defects in axon pathfinding and synaptic connectivity, paralleled by expression defects of molecules involved in axon pathfinding, cell-cell recognition, and synaptic connectivity. We conclude that unc-42 establishes functional circuitry by acting as a terminal selector of functionally connected neuron types. We identify a number of additional transcription factors that are also expressed in synaptically connected neurons and propose that terminal selectors may also function as ‘circuit organizer transcription factors’ to control the assembly of functional circuitry throughout the nervous system. We hypothesize that such organizational properties of transcription factors may be reflective of not only ontogenetic, but perhaps also phylogenetic trajectories of neuronal circuit establishment.